Is it hot enough? A multi-proxy approach shows variations in cremation conditions during the Metal Ages in Belgium. (December 2021) - Stamataki, Elisavet; Kontopoulos, Ioannis; Salesse, Kevin; McMillan, Rhy; Veselka, Barbara; Sabaux, Charlotte; Annaert, Rica; Boudin, Mathieu; Capuzzo, Giacomo; Claeys, Philippe; Dalle, Sarah; Hlad, Marta; et al.
Abstract: Studies of funerary practices provide information about many aspects of death in past societies. However, only limited archaeological evidence documents the circumstances under which cremations occurred and the person(s) who were performing the funerary rituals. Lying at the border between Atlantic and Continental cultural traditions, the Scheldt and Meuse basins of Belgium represent a unique location to investigate variations in ancient pyre technology and body management, as well as the transfer of knowledge related to cremation techniques during the Metal Ages (ca. 2100-52 BCE). The combined use of Fourier Transform Infrared spectroscopy, and carbon and oxygen isotope analysis of different skeletal elements from cremation deposits from four archaeological sites clearly shows differences between the Meuse and Scheldt basins. Different wood availability or selection, and variations in the skills and/or experience of the cremation operator may explain these results. These observed differences are likely linked to ways in which cremation was performed in the two basins, indicating that during the Metal Ages, burning processes were not homogeneous in the Belgian region. Instead, cremation practices appear to align with the different cultural influences also observed in ceramics and bronze artifacts from the same time period. These observed differences in funerary practices between the two basins in Belgium show the immense potential of combining infrared and carbon and oxygen isotope analyses to investigate cremation rituals in any period and region around the world. Highlights: Cremation is the dominant funerary practice in Belgium during the Metal Ages. Multi-proxy/sampling analyses reveal differences in cremation practices. Chemical and structural changes on burnt bones show variations in burning conditions. Cultural differences were observed in cremation practices in Belgium.